Prevalence of Antimicrobial Resistance (AMR) Salmonella spp. and Escherichia coli Isolated from Broilers in the East Coast of Peninsular Malaysia - Shamsaldeen Ibrahim; Loh Wei Hoong; Yip Lai Siong; Zaharuddin Mustapha; C. W. Salma C. W. Zalati; Erkihun Aklilu; Maizan Mohamad; Nor Fadhilah Kamaruzzaman (MDPI AG, 2021)
Salmonella species (spp.) and Escherichia coli (E. coli) are the most common infectious pathogens in poultry. Antimicrobials are given either as growth promoters or as treatment, thereby increasing the possibility of the emergence of antimicrobial resistance (AMR). We determined the prevalence of AMR for both pathogens isolated from broiler farms in the East Coast of Peninsular Malaysia from 2018-2019. A total of 384 cloacal swabs were collected, followed by bacterial isolation, confirmation, and antimicrobial susceptibility tests. The overall prevalence of Salmonella spp. and E. coli were 6.5% and 51.8%, respectively. Salmonella spp. and E. coli displayed resistance towards the following antimicrobials: erythromycin (100% for both pathogens), chloramphenicol (76.2% and 84.5%, respectively), tetracycline (62% and 94.6%, respectively), ampicillin (47.7% and 87%, respectively), sulfamethoxazole/trimethoprim (42.9% and 83.3%, respectively), ciprofloxacin (4.8% and 23.8%, respectively), nalidixic acid (9.6% and 60.7%, respectively), streptomycin (19% and 66%, respectively), kanamycin (28.6% and 57%, respectively), cephalothin (0% and 11%, respectively), and gentamicin (0% and 20.2%, respectively). Multidrug resistance (MDR) was recorded in 82% of Salmonella spp. and 100% of E. coli. These findings demonstrate the high prevalence of AMR in both pathogens in broiler farms on the East Coast of Peninsular Malaysia. These findings could be attributed to the excessive use of antimicrobial agents by poultry farm owners. Enhanced control measures and a strong monitoring system should be urgently implemented in order to reduce the emergence of antimicrobial resistance.